(3QSGdI aj HjGf MTQ GdCLSGOs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYHGO efg GdeHOC hGdeYGO hHYO agPg QSGdI eQJHI ai HjGf GdeYGO GdLSeGfi hJaUjd eG hbY ef GdNdGa Hjf GdSda s
(3BNQgG (B:s
(3hde jOQ Cf GddGRe ai GdOhQ gh Cf jchf GdTF ehLhOkG bHd Cf jchf ehLhOkG GHJOGkA hgPG eSJMjd HGdHOjgI ShGA cGf GdbHdjI PGJjI Ch ReGfjI hajeG fMf ajg dGjdRe eG PcQ Hd jdRe Cf jYhO hLhO GdTF HYO eG RGd Yfg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B19s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJhMjO hGdedd hGdfMds